WORK CONTENT TRENDS IN INITIAL DEVELOPMENT OF RUSSIAN SPEECH IN EDUCATIONAL CONDITIONS - Yurtaev, Sergey; Ismailowa, Raniya; Kolichewa, Galina (Revista Inclusiones, 2020)
The purpose of the study is to theoretically substantiate the model of Russian speech initial development in the context of teaching children 7 to 11 years of age. The reason for creating the given model is a contradiction between the potential achieved by historical development of methodological science and programme state documents; the need for bachelors to develop their readiness for pedagogical activity, and the insufficiently developed issues of implementing the programme state material. The approach to achieving this goal includes comparative analysis of wellknown scientists’ works, documents, and written works of schoolchildren of nearest development zone (of 12 to 16 years of age). This approach makes it possible to identify direction of forming pedagogical thought, its changes, stable, transient signs of students’ speech, and its difficulties.